PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS POWERPOINT MATERI ENERGI DAN PERUBAHANNYA KELAS III SEKOLAH DASAR NEGERI 37/II PASAR LUBUK LANDAI KABUPATEN MUARA BUNGO - Amril; Lika Apreasta; Wawan Gunawan (STKIP Subang, 2023)
The purpose of this study was to develop Powerpoint learning media on energy material and its changes in class III SDN 37/II Lubuk Landai Market, Muara Bungo Regency. The purpose of the research was because there were several problems that were found by researchers when carrying out research, namely the learning process that only used teacher manuals and conventional learning methods such as the lecture method. The lack of enthusiasm of students in student learning is also often individual, noisy and does not pay attention to the teacher when explaining. This study uses the ADDIE Research and Development (R&D) model which has 5 sections, namely: Analysis, Design, Development, Implementation, Evaluation. The type of data used is in the form of quantitative and qualitative data. Instrument Development uses validity and practicality instruments. Data collection techniques using interviews, observation, questionnaires and documentation. The analysis technique used uses validity, practicality and effectiveness. The final results of this study can be concluded that the product development process, namely in the form of Powerpoint learning media on energy material and its changes in class III SDN 37/II Lubuk Landai Market, Muara Bungo Regency was declared valid by 6 experts to proceed to the next stage. The products developed are also stated to be practically used in learning activities by teachers and students. The use of the products developed was able to improve student learning outcomes, this is in line with student learning outcomes that of the 20 students who took part in learning using the media developed in material 1, it was stated that 85% completed material 2, which was stated to be 85% complete, and material 3, which was obtained 90% complete.